FINANCIAL MANAGEMENT MODELING FOR ENTERPRISES - Natalia Wasilewska; Nadiia Davydenko (Polityki Europejskie, Finanse i Marketing)
The purpose of the study was to model the financial management processes of enterprises to ensure the qualitative and complete forecasting of enterprise development. The analysis of the strategic matrix of interconnections through the use of power, logarithmic and polynomial trends during the determination of the tightness of the connection between the financial resources’ volumes and the coefficients of liquidity and financial sustainability at the enterprise was carried out. It is established that effective organization of scenario activity as an element of strategic planning is one of the main factors that will allow improving the system of financial management at the enterprise.